The impact of oral food challenges for food allergy on quality of life: A systematic review. Issue 5 (16th May 2018) - Kansen, Hannah M.; Le, Thuy‐My; Meijer, Yolanda; Flokstra‐de Blok, Bertine M. J.; Welsing, Paco M. J.; van der Ent, Cornelis K.; Knulst, André C.; van Erp, Francine C.
Abstract: Background: Food allergy significantly impairs health‐related quality of life (HRQL). Currently, it is still unknown whether diagnostic interventions for food allergy improve HRQL. We aim to assess the impact of diagnostic interventions for food allergy on HRQL. Methods: A systematic search was performed in MEDLINE, Embase, Cochrane Library, and CINAHL focused on patients with a (suspected) food allergy who underwent diagnostic interventions (ie, skin prick test, specific IgE, or oral food challenges [OFC]) and in whom HRQL was assessed. The mean difference between HRQL before and after the diagnostic intervention was calculated. A minimal clinically important difference of 0.5 was considered clinically relevant for the food allergy quality of life questionnaire. Results: Seven of 1465 original identified publications were included in which the impact of an OFC on HRQL was investigated (total patients n = 1370). No other diagnostic interventions were investigated. Food allergy‐specific parent‐reported HRQL improved significantly after an OFC irrespective of the outcome in children with a suspected food allergy in two publications. The change was considered clinically relevant in one of two publications. In addition, parent‐reported HRQL improved after an OFC to assess the eliciting dose in children with a confirmed food allergy. The parental burden was significantly reduced after an OFC to assess resolution of food allergy. A meta‐analysis could not be performed due to the limited numbers of, and considerable heterogeneity between, eligible publications. Conclusion: An OFC is associated with an improved food allergy‐specific HRQL and a reduced parental burden of food allergy. Abstract :